2012
DOI: 10.1115/1.4005160
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of Thermal Emission by Use of Micro and Nanoscale Structures

Abstract: In high temperature and vacuum applications, for which heat transfer is predominantly by radiation, the material’s surface texture is of substantial importance. Several micro and nanostructures designs have been proposed to enhance a material’s emissivity and its radiative coherence. Control of thermal emission is of crucial concern in the design of infrared sources, in electronic chip coolants, in high-efficiency photovoltaic cells, and in solar energy conversion. In this review paper, we present microscale a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…Radiative material properties are famously sensitive, however, and in some cases, ill-defined, often leading to suboptimal application. Further, the most recent decade of research has revealed additional strong dependencies of radiative properties in the near-field in which bulk properties can be dramatically different based on surface structuring at the micro-and nanoscale [1][2][3][4][5][6][7][8]. This sensitivity is a double-edged sword, creating a difficult challenge for analytical or computational design of a nanostructured surface, yet providing the opportunity to tailor precise, coherent properties to manage radiative energy in intelligent ways.…”
Section: Introductionmentioning
confidence: 99%
“…Radiative material properties are famously sensitive, however, and in some cases, ill-defined, often leading to suboptimal application. Further, the most recent decade of research has revealed additional strong dependencies of radiative properties in the near-field in which bulk properties can be dramatically different based on surface structuring at the micro-and nanoscale [1][2][3][4][5][6][7][8]. This sensitivity is a double-edged sword, creating a difficult challenge for analytical or computational design of a nanostructured surface, yet providing the opportunity to tailor precise, coherent properties to manage radiative energy in intelligent ways.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal sources with geometries that provide matching of the high momentum of these surface modes to the free space radiation may exhibit even longer coherence length than planar near-field emitters made of the same material [180,181]. These coherent far-field direc- [194], ©APS), (e) a periodic photonic crystal lattice with embedded GaAs quantum wells (reproduced with permission from [71], ©AIP), and (f) a graphene sheet embedded into a planar Fabry-Perot cavity (reproduced with permission from [200], ©NPG).…”
Section: Nanophotonic Incandescent Sources: Coherent Polarized and mentioning
confidence: 99%
“…This value exceeds the coherence length of the blackbody emission and is approaching a coherence length of a CO 2 laser. Other coherent thermal emitters based on periodic one-dimensional gratings and two-dimensional photonic crystals with emission peaks observed in near-to-far-IR frequency range have been demonstrated experimentally by using metals and polar dielectrics [180,181,[184][185][186][187][188][189].…”
Section: Nanophotonic Incandescent Sources: Coherent Polarized and mentioning
confidence: 99%
See 2 more Smart Citations